2018
DOI: 10.1007/s00205-018-1318-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Stress Concentration in the Presence of Closely Spaced Hard Inclusions in Two-Dimensional Linear Elasticity

Abstract: In the region between close-to-touching hard inclusions, the stress may be arbitrarily large as the inclusions get closer. The stress is represented by the gradient of a solution to the Lamé system of linear elasticity. We consider the problem of characterizing the gradient blow-up of the solution in the narrow region between two inclusions and estimating its magnitude. We introduce singular functions which are constructed in terms of nuclei of strain and hence are solutions of the Lamé system, and then show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…For the elasticity problem, Bao et al obtained an upper bound in two dimensions [16], and this result was generalized to higher dimensions [17]. Recently, the gradient blow-up term of the solution in two dimensions was verified for convex hard inclusions by Kang and Yu [24] and for circular holes by Lim and Yu [35].…”
Section: Introductionmentioning
confidence: 99%
“…For the elasticity problem, Bao et al obtained an upper bound in two dimensions [16], and this result was generalized to higher dimensions [17]. Recently, the gradient blow-up term of the solution in two dimensions was verified for convex hard inclusions by Kang and Yu [24] and for circular holes by Lim and Yu [35].…”
Section: Introductionmentioning
confidence: 99%
“…For examples, it has been shown that the order of blow-up (field enhancement) of ∇u is ǫ −1/2 in two dimensions [4,17] and (ǫ| log ǫ|) −1 in three dimensions [6]. We refer to references in a recent paper [8] for more comprehensive list of references. The problems (1.1) and (1.5), especially their unique solvability, can be investigated in a unified way.…”
Section: Introduction and Statements Of Resultsmentioning
confidence: 99%
“…The novelty of the proof lies in the construction of test functions, especially those for the dual principle. The test functions for the dual principle are constructed using singular functions introduced by authors in [7]. These functions are elaborated linear combinations of nuclei of strain and capture precisely stress concentration between two adjacent hard inclusions.…”
Section: Introductionmentioning
confidence: 99%